2012
DOI: 10.5999/aps.2012.39.2.113
|View full text |Cite
|
Sign up to set email alerts
|

Absorbable Plate as a Perpendicular Strut for Acute Saddle Nose Deformities

Abstract: BackgroundNasal pyramid fractures accompanied by saddle nose deformities are not easily corrected by closed reduction. We used an absorbable plate as a perpendicular strut to support the collapsed "keystone area" and obtained good results.MethodsBetween September 2008 and June 2011, 18 patients who had nasal pyramid fractures with saddle nose deformities underwent surgery. Pre- and postoperative facial computed tomographic images and photographs were taken to estimate outcomes. The operative technique included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…28 For such reasons, methods have also been introduced that support the remaining L-strut using an absorbable plate as batten after harvesting as much as septal cartilage as possible. 15 , 29 , 30 Likewise, even when the maximum amount of septal cartilage is obtained in Asians, grafting diced cartilage with DTF for the full length of the dorsum without utilizing rib cartilage is vastly insufficient in many cases, as most of the cartilage would be consumed for tip plasty. Furthermore, patients who undergo reoperation or who have had septal injury lack septal cartilage; thus, most of the diced cartilage graft with DTF is mainly utilized in the correction of radix graft or dorsal tip irregularity.…”
Section: Discussionmentioning
confidence: 99%
“…28 For such reasons, methods have also been introduced that support the remaining L-strut using an absorbable plate as batten after harvesting as much as septal cartilage as possible. 15 , 29 , 30 Likewise, even when the maximum amount of septal cartilage is obtained in Asians, grafting diced cartilage with DTF for the full length of the dorsum without utilizing rib cartilage is vastly insufficient in many cases, as most of the cartilage would be consumed for tip plasty. Furthermore, patients who undergo reoperation or who have had septal injury lack septal cartilage; thus, most of the diced cartilage graft with DTF is mainly utilized in the correction of radix graft or dorsal tip irregularity.…”
Section: Discussionmentioning
confidence: 99%
“…Most literatures indicate that pHDPE was used as a spreader graft, and that the complication rates were significantly lower compared to when pHDPE was used as a columellar strut. 16 , 17 , 18 , 19 , 20 Based on their bivariate analysis, Winkler, et al 21 reported that the relative risk of postoperative infection from the use of pHDPE as a columellar strut was 21.24%, being approximately 5 times higher than 4.11% shown with the use of expanded polytetrafluoroethylene as the dorsal onlay. Our own experiences indicate that the surgical removal of Medpor® was extremely complicated compared to that of other alloplastic materials.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the development of many synthetic biomaterials such as silicone, poly-tetrafluorethylene (PTFE), poly-L-glycolic acid (PLGA), poly-caprolactone (PCL) and poly-L-lactic acid (PLLA) ( 9 , 10 ). In addition, natural polymers, such as chitosan, collagen, chitin, gelatin and conducting polymers, such as polypyrrole, polyaniline or polythiophene derivatives, are also widely used for nerve regeneration ( 11 , 12 ). Nevertheless, they have a lack of the effects in inducing the nerve regeneration.…”
Section: Introductionmentioning
confidence: 99%